"Everybody Was Included in the Conversation": Teachers' Perceptions of Student Engagement in Transdisciplinary STEM Learning in Diverse Elementary Schools - Nancy M. Holincheck; Tammy Kraft; Terrie M. Galanti; Courtney K. Baker; Jill K. Nelson (MDPI AG, 2024)
This qualitative interview study examines STEM integration in three diverse elementary schools through the eyes of the teachers and instructional coaches (n = 9) who facilitated the transdisciplinary Box Turtle Model-eliciting Activity (MEA). Prior to implementation, participants attended a full-day professional development workshop in which they experienced the MEA in school-based triads of principals, coaches, and teachers. The educators then implemented the MEA with elementary students from across multiple grade levels. We used the guiding principles of productive disciplinary engagement in our analysis of educator interviews to interpret participants' perceptions of how an MEA encourages elementary students to (a) problematize real-world scenarios, (b) direct their own learning, and (c) collaborate through meaningful academic discourse. Educators also identified challenges to integrating STEM in elementary classrooms. The Box Turtle MEA offered more equitable access to STEM by positioning students as authorities and providing space for them to be accountable to themselves and others in solving an authentic, real-world problem.